Effect of commercial logging on Pinus jaliscana, a species listed as threatened - Paredes Lara, María del Rosario; Mendoza Briseño, Martín Alfonso (Instituto de Ecología, A.C., 2018)
Active management has been touted as a desirable option for endangered species that are commercially valuable. The case presented here is about the Jalisco pine (Pinus jaliscana Pérez de la Rosa), an endangered species of Mexico. This pine is an important component in the production of wood within a protected natural area. The historical record of the selected study case, a forest dominating P. jaliscana, shows that the events that led to this species be listed, occur in populations far from where the species is subject to commercial extraction programs. A monitoring and evaluation network has been set up to monitor responses to treatments from a silvicultural regime designed to overcome the anthropogenic stressors. Available results indicate that the silvicultural regime is driving the forest away of the commercial objectives and of the recovery of the species in the territory of its geographical distribution. The message in this research is that even if conservation measures were designed to effectively correct the human causes of the deterioration and potentiality of some species at risk, the unique details that prevail in each habitat corner can create peculiar scenarios, where general rules must be adjusted.